Pendampingan Penyusunan SOM dan SOP KSP â€œAmerta Bumiâ€ di Desa Sampalan Klod Kecamatan Dawan Kabupaten Klungkung - Ni Made Santini; Ni Made Taman Sari; Made Pratiwi Dewi (Lembaga Pengabdian Kepada Masyarakat, Universitas Warmadewa, 2021)
The vision of the local government of Bali is Nangun Sat Kerthi Loka Bali, which maintains the preservation and harmony of nature and its contents, to realize a prosperous and happy Balinese manners on the scale of a life that is politically sovereign and economically independent, one of the economic activities that can lead to nagun sat kerthi. loka bali is a movement from the Bali Province Cooperatives and SMEs Service that seeks to deliver on a mission (1) Creating quality and healthy Cooperatives (2) Fostering entrepreneurship of Cooperatives and SMEs (3) Facilitating financing and guarantees for Cooperatives and SMEs and (4) Increasing Partnerships Cooperatives and SMEs. Cooperatives can provide tremendous benefits that can reduce movements and missions, especially in Indonesia. If the cooperative can be managed properly, clearly, openly, and voluntarily in the name of the family, the cooperative that is running will be able to fulfill its main objectives. Cooperative performance is very important to pay attention to for the health of the cooperative itself. So that cooperatives can be sustainable in carrying out their activities, it is important for every buyer to have as an operational reference the SOM concept and SOP. The weakness of regional cooperatives is that most do not have a SOM and SOP so that in running a business there is no reference that is used as a guideline. Solutions to existing problems will be assisted in service activities. By providing assistance in â€œPreparing SOM and SOPs for Business Entities, Institutional SOPs, SOPs for Fund Distribution so that cooperatives can carry out their functions in accordance with SOM and SOPs according to applicable regulations. The implementation of service activities carried out with mentoring method activities is how to prepare SOM and SOP according to the guidelines from the Cooperatives, MSMEs and Trade Office.